The relevance of sustainability labeling for Chinese consumers perception of the luxuriousness of, and purchase intent for sustainabilitu-labelled exotic leather accessories - De Klerk, Helena Maria (University of Pretoria, 2020)
Dissertation (MConsumer Science)--University of Pretoria, 2019.